Pemberdayaan Masyarakat melalui Pelatihan Pengolahan Limbah Rumah Tangga menjadi Produk BioCleaner Ramah Lingkungan - Mardina, Vivi; Dwitya, Yonadiah; Lestari, Ratna; G Wibowo, Sara; Al Fajar, Beni; Fitriani, Fitriani; Y Persada, Andri; A Putri, Kartika; PE Sari, Herlina; Fadly, T Andi; Faji, Rahmatul; Arico, Zulfan; Rahmawati, Rahmawati; Mirfa, Enny; Oktaviodes, Alfiandinov (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The village of Air Masin relies economically on the agricultural sector, particularly rice and horticultural crops. However, the community’s welfare level remains low, prompting many residents to seek additional income through small-scale enterprises. Unfortunately, limited knowledge and skills in managing these businesses hinder the potential for local economic development. Moreover, public awareness regarding environmentally friendly waste management remains minimal, leading to environmental pollution and posing health risks. Women, especially members of the Family Welfare Movement (PKK), lack an understanding of how to effectively manage household waste. In fact, such waste can be processed into economically valuable products such as eco-enzymes, liquid organic fertilizers, animal feed, and soap. This study aims to empower PKK women through training in processing household waste into biocleaners natural cleaning products made from domestic organic waste. The training is expected to enhance the participants' skills in converting waste into eco-friendly products that can be marketed, thereby creating new economic opportunities. In addition, biocleaners help reduce environmental pollution and dependency on harmful chemical-based cleaning agents. Data analysis was conducted using both qualitative and quantitative approaches. The results indicate a significant increase in participants’ understanding of the basic concepts of biocleaners as environmentally friendly cleaning products. There was a 100% improvement in participants' skills in processing household waste into biocleaners, and growing interest in adopting this technology as an alternative to conventional chemical cleaners. This initiative demonstrates that environmental education not only improves knowledge but also drives behavioral change and fosters self-reliance at both household and community levels.